ANALISIS PENERAPAN METODE PENCATATAN DAN PENILAIAN ATAS PERSEDIAAN BARANG DAGANG MENURUT PSAK NO 14 REVISI TAHUN 2012 PADA PT. BUMI PEMBANGUNAN PERTIWI - Arik Wijayani (INVENTORY: JURNAL AKUNTANSI, 2017)
Inventory is an important thing for the company because most of the company's assets embedded in inventories. Problems are often experienced in accounting for inventories is the recording and assessment. The purpose of research at PT. Bumi Pertiwi Development is to investigate the suitability of the application of the method of recording and valuation of inventory at PT . Bumi Pertiwi Development with Statement of Financial Accounting Standards ( SFAS) No. 14 Revised 2012.This study uses a qualitative method. Data collection techniques with interviews and observations and documentation , and then analyzed using methods deskripstif and comparing the application of methods of recording and valuation of merchandise inventory PT . Bumi Pertiwi Development with IAS 14 Revised in 2012 .The study concluded that the method of recording using perpectual methods and methods of assessment using the average method. Inventory recording method applied by PT . Bumi Pertiwi Development is not in accordance with IAS 14 Revised, 2012.While inventory valuation method PT . Bumi Pertiwi development is in accordance with IAS 14 Revised 2012. Keywords : methods of recording perpectual, average valuation methods and PT . Bumi Pertiwi Development